Gonadal disruption after single dose exposure of prothioconazole and prothioconazole-desthio in male lizards (Eremias argus). (December 2019) - Xie, Yun; Jiang, Haotian; Chang, Jing; Wang, Yinghuan; Li, Jianzhong; Wang, Huili
Abstract: Prothioconazole (PTC) is a widely used triazole fungicide with low toxicity, and its desulfurization metabolite, prothioconazole-desthio (PTC-d), is reported to have higher reproductive toxicity to mammals. However, little is known about the reproductive toxicity, much less endocrine disrupting effect, of these two chemicals on reptiles. In this study, we investigated the effects of single dose of PTC/PTC-d (100 mg kg −1 body weight) exposure on the pathomorphism of testes and epididymides, serum sex steroid hormones (testosterone and 17β-estradiol) and transcription of steroidogenic-related genes ( STARD, cyp11A, cyp17, cyp19A, 17β-HSD, 3β-HSD, AR and ER-α ) in gonads of male lizards ( Eremias argus ). Although structural disorder existed in PTC-d exposure group, severe gonadal disruption, especially suppression of spermatogenesis was only observed in testis after PTC treatment, which consequently led to the lack of spermatozoa in epididymal ducts. Consistent with this result, T/E2 value in PTC exposure was elevated to a significant higher level compared with control and continually increased over time, while T/E2 value in the PTC-d exposure group slightly increased only at 12 h. These results demonstrated a more serious disruption of PTC on male lizard gonads than PTC-d. In addition, the expression of cyp17 gene was inhibited at 6 h, however, was induced at 12 h, and exhibited negative correlations with STARD, cyp11A and 3β-HSD after PTC exposure at each timepoint. In PTC-d group, the expression of STARD and 3β-HSD were significantly down-regulated, in contrast, cyp11A and cyp17 were up-regulated, and each gene showed consistent changes over time. For 17β-HSD, no significance was observed in both treated groups. This study was the first to compare the gonadal disruption of PTC and PTC-d in male lizards and elucidated that these two chemicals influenced the physiological function of male gonads through differential transcriptional modulation. Graphical abstract: Image 1 Highlights: PTC induced more serious pathologic changes of gonad than PTC-d in male lizards. Spermatogenesis was suppressed after treated by PTC. The elevation of serum T and E2 levels caused by PTC was more drastic than PTC-d. PTC and PTC-d caused gonadal disruption through different transcriptional modulation. Abstract : PTC exposure induced more serious negative effect on male lizards' gonads than its metabolite PTC-d.